Survival, DNA, and Ultrastructural Integrity of a Cryptoendolithic Antarctic Fungus in Mars and Lunar Rock Analogues Exposed Outside the International Space Station - Onofri, Silvano; Selbmann, Laura; Pacelli, Claudia; Zucconi, Laura; Rabbow, Elke; de Vera, Jean-Pierre (Astrobiology, 2019)
The search for life beyond Earth involves investigation into the responses of model organisms to the deleterious effects of space. In the frame of the BIOlogy and Mars Experiment, as part of the European Space Agency (ESA) space mission EXPOSE-R2 in low Earth orbit (LEO), dried colonies of the Antarctic cryptoendolithic black fungus Cryomyces antarcticus CCFEE 515 were grown on martian and lunar analog regolith pellets, and exposed for 16 months to LEO space and simulated Mars-like conditions on the International Space Station. The results demonstrate that C. antarcticus was able to tolerate the combined stress of different extraterrestrial substrates, space, and simulated Mars-like conditions in terms of survival, DNA, and ultrastructural stability. Results offer insights into the habitability of Mars for future exploration missions on Mars. Implications for the detection of biosignatures in extraterrestrial conditions and planetary protection are discussed.